2020
DOI: 10.1016/j.ajic.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extended use and decontamination with vaporized hydrogen peroxide on N95 respirator fit

Abstract: Highlights We evaluated the impact of extended use and H 2 O 2 decontamination on N95 respirators. Extended N95 use and decontamination was associated with a rapid loss of fit test. User seal check overestimated user fit test. Single-use N95 respirator longevity may be shorter than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 7 publications
2
46
0
Order By: Relevance
“…All included studies analyzed N95 model FFRs. 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 Additionally, 1 investigation employed FFR P100, 7 another used PFF-3, 20 and 7 also used surgical masks. 5 , 16 , 21 , 22 , 23 , 31 , 41 More than half of the studies included in this review received funding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All included studies analyzed N95 model FFRs. 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 Additionally, 1 investigation employed FFR P100, 7 another used PFF-3, 20 and 7 also used surgical masks. 5 , 16 , 21 , 22 , 23 , 31 , 41 More than half of the studies included in this review received funding.…”
Section: Resultsmentioning
confidence: 99%
“…The preservation of material integrity was assessed in 22 studies (55.0%). 4 , 5 , 7 , 10 , 13 , 15 , 17 , 19 , 20 , 21 , 22 , 23 , 25 , 26 , 28 , 29 , 30 , 33 , 35 , 39 , 41 , 44 It can be observed that the use of hydrogen peroxide, 4 , 13 , 19 , 32 , 35 especially Hydrogen Peroxide Gas Plasma, 4 , 19 and high-temperature methods 10 , 15 , 16 , 19 , 23 , 25 , 26 , 28 , 41 were strongly associated with integrity degradation. Sodium hypochlorite also damaged the FFRs, causing stains, discoloration, dissolution of the nose seal comfort pad, oxidation, and stiffening of the filter and elastic 7 , 10 , 15 , 16 , 19 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide Hydrogen peroxide was evaluated in its liquid, plasma and gas/vapor forms by nineteen laboratory studies. 33,[40][41][42][43][44]48,52,[58][59][60][61][62]65,66,69,73,75,76 . The effect of hydrogen peroxide on the ltering capacity varied according to the method used.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen peroxide Hydrogen peroxide was evaluated in its liquid, plasma and gas/vapor forms by nineteen laboratory studies. 28,[35][36][37][38][39]43,47,[53][54][55][56][57]60,61,64,68,70,71 The effect of hydrogen peroxide on the ltering capacity varied according to the method used. Hydrogen peroxide plasma led to changes in the masks' metallic nasal clips 61 and degradation in their ltering performance.…”
Section: Characterization Of the Included Studiesmentioning
confidence: 99%